Boron‐dependent regulation of translation through AUGUAA sequence in yeast - Tsednee, Munkhtsetseg; Tanaka, Mayuki; Kasai, Koji; Fujiwara, Toru (Yeast (Chichester, England), 2020)
Under high boron (B) conditions, nodulin 26‐like intrinsic protein 5;1 (NIP5;1) mRNA, a boric acid channel, is destabilized to avoid excess B entry into roots of Arabidopsis thaliana. In this regulation, the minimum upstream open reading frame (uORF), AUGUAA, in its 5′‐untranslated region (5′‐UTR) is essential, and high B enhances ribosome stalling at AUGUAA and leads to suppression of translation and mRNA degradation. This B‐dependent AUGUAA‐mediated regulation occurs also in animal transient expression and reticulocyte lysate translation systems. Thus, uncovering the ubiquitousness of B‐dependent unique regulation is important to reveal the evolution of translational regulation. In the present study, we examined the regulation in Saccharomyces cerevisiae. Reporter assay showed that in yeast, carrying ATGTAA in 5′‐UTR of NIP5;1 upstream of the reporter gene, the relative reporter activities were reduced significantly under high B conditions compared with control, whereas deletion of ATGTAA abolished such responses. This suggests that AUGUAA mediates B‐dependent regulation of translation in Saccharomyces cerevisiae. Moreover, the deletion of ATGTAA resulted in up to 10‐fold increase in general reporter activities indicating the suppression effect of AUGUAA on translation of the main ORF. Interestingly, mRNA level of the reporter gene was not affected by B in both yeast cells with and without AUGUAA. This finding reveals that in yeast, unlike the case in plants, mRNA degradation is not associated with AUGUAA regulation. Together, results suggest that B‐dependent AUGUAA‐mediated translational regulation is common among eukaryotes.